Investors Rationality for IPOs Using Meta Analysis and Forest Plots in Neyeloff et al. (2012) Framework: An Investigation. (March 2015) - Jindal, Mani; Chander, Ramesh
This research article focuses on the contours of investors' rationality as regard to the initial public offering (IPO). For last 20 years, financial world has been very volatile. Now the investors have actively started to participate in the investment activities. The investment markets are becoming more risky; time makes investors to behave differently. It is crucial to perceive the responses of the investors and to identify the factors of the investment decisions. This research article is to generalise research findings emanating from the research on the investors rationality conducted during 2001 to 2012. To achieve the objective of this study, the previous 20 research studies is taken as a sample; meta analyses is used as a statistical tool for analysing the data and to get results whether the investors are rational (or not) in making investment decisions in the IPOs market. And the result indicates that the meta analysis matches with the sample data and shows that the investors are rational for investing in the IPOs.